Blood Management System Android Application - Mal, Sandip; Gujar, Deepak (International Journal of Computer Sciences and Engineering, 2019)
The mobile applications to solve problems for us is not new to us in today’s world. One of the major problems in the field of medical today is to find a convenient way to look for blood donors and receivers in case of an emergency. This is an android application developed in order to solve this major problem. It helps you look for blood donors and receivers and track nearest hospital, fire station, ambulance and police station of the specific location in your city and connects you with them instantly in need. User can call to emergency numbers and call his home and his emergency contact person in single button click. In order to make sure the application is widely used even in remote areas the user interface has been kept extremely simple. This Application runs on the latest Android OS and has an extremely small size of 2.5Mb.